2019
DOI: 10.1186/s13052-019-0704-0
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncityal Virus A and B: three bronchiolitis seasons in a third level hospital in Italy

Abstract: Background Respiratory syncytial virus (RSV) is the main cause of hospitalization for bronchiolitis among infants. RSV is classified into two subtypes, A and B, whose predominance alternates during different epidemic seasons. The clinical impact of viral factors is controversial and many evidences suggest a critical role for the immune host response. Premature children are at the highest risk for severe RSV infection. The main aim of this study is to identify the different RSV subtypes circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…The relevant role of RSV as the major etiologic agent of bronchiolitis was already described by an Italian group in 2014, and the burden of RSV-associated admission is confirmed by a prospective multicenter study performed in Spain, proving that costs were significantly higher in children positive to RSV ( 19 , 20 ). Moreover, in a recent study, we reported an increase in PICU admission rates due to RSV-bronchiolitis ( 21 ).…”
Section: Discussionmentioning
confidence: 93%
“…The relevant role of RSV as the major etiologic agent of bronchiolitis was already described by an Italian group in 2014, and the burden of RSV-associated admission is confirmed by a prospective multicenter study performed in Spain, proving that costs were significantly higher in children positive to RSV ( 19 , 20 ). Moreover, in a recent study, we reported an increase in PICU admission rates due to RSV-bronchiolitis ( 21 ).…”
Section: Discussionmentioning
confidence: 93%
“…Most studies have focused on hospitalised infants, some have excluded high‐risk children, some have sampled from short time periods, and various measures of disease severity have been used. Of studies that did find a difference, most suggest that RSV‐A infection is associated with greater disease severity in children when compared to RSV‐B infection 1,9–14 …”
Section: Discussionmentioning
confidence: 99%
“…Another large, prospective study found that RSV‐A positive infants presenting to the emergency department were more likely to be admitted to hospital compared to RSV‐B positive infants 9 . Some studies concluded that RSV‐A was associated with more severe disease in preterm children 10 or that RSV‐A infected infants were significantly younger 14 . Other studies have calculated composite severity scores demonstrating that RSV‐A infection is associated with greater disease severity 12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the predominance of RSV subtypes in other European countries during the same winter seasons varied. In Italy, RSV-B predominated in 2016–2017 and RSV-A predominated in 2017–2018 [20], whereas in Catalonia, Spain, RSV-B was more prevalent than RSV-A during both seasons, with strains mainly classified into the BA9 and ON1 genotypes, respectively [21]. In Bulgaria, RSV-B predominated during both seasons (2016–1018) [22].…”
Section: Discussionmentioning
confidence: 99%